KEBATINAN JAWA SEBAGAI PRODUK INTERNALISASI NILAI-NILAI TASAWUF: SEBUAH IMPLEMENTASI METODE DAKWAH â€œBILHIKMAHâ€ DALAM QS. AN-NAHL AYAT 125 - Umatin Fadilah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
Islam constitutes rahmatan lil ‘ alamin religion. With the title that is slung, Islam shall point out its existence as an universal religion who can get dialectic with local wisdom. Therefore, Islam shall have mission method that can accomodate local points. In Qur’an, concept about mission which gets local wisdom basis that most decants deep Qur’an surah an-Nahl verse 125. This writing works through about the implementation of da’wa bil-hikmah’s concept in get interaction with local culture, notably Javanese culture, is next result mystical Javanese as internalitation product of Islamic tasawuf’s points.